Russian prefixes as an element of the national language picture of the world in comparison with the Armenian - HARUTYUNYAN, VERONIKA (Bulletin of Yerevan University H: Russian Philology, 2021)
Russian prefixes as an element of the national language picture of the world in comparison with the Armenian. – The articleconsiders Russian prefixes as an element of the national language picture of the world. Comparison of such prefix words with the Armenian language shows that their meanings in bilingual dictionaries are either not differentiated or transmitted in other words.
Keywords: russian language picture of the world, space, prefixes, meanings